Impacto de la gestión del talento humano en el desempeño organizacional de quevial ep. del cantón Quevedo. Año 2023 - Calvache Montesdeoca, Ariana Alexandra (2024)
This research analyzes the incidence of human talent management and organizational performance in the company QUEVIAL EP. from the Quevedo canton. Human Talent management is to create an intrinsic connection between the company with its policies and the workers with their skills, its purpose is to exploit the relationship of both parties to achieve adequate organizational performance that is measured in the achievement of objectives. The applied methodology was based on a descriptive approach, as well as inductive, deductive and analytical, which exposed a series of events and criteria, which reflected the most relevant factors according to the objectives set, through the application of techniques such as interviews, surveys. and direct observation, fundamental primary information was generated. The results indicated that human talent management responds to the organization and the resources available for its execution, as well as the reaction of collaborators to the absence of leadership or representation that ensures the economic situation and the aspects that affect internal management. The politicization of the company implies a rotation of administrators that does not contribute to job stability and currently a fragile economic situation, which has had a negative impact on organizational performance, there is no clear perspective of the processes due to not having the necessary resource. It is recommended according to the results, to present the observations of the collaborators through human talent management that links the institutional needs as well as those of the workers to improve organizational performance.